2018
DOI: 10.1111/fwb.13216
|View full text |Cite
|
Sign up to set email alerts
|

Understanding variation in salamander ionomes: A nutrient balance approach

Abstract: Ecological stoichiometry uses information on a few key biological elements (C, N and P) to explain complex ecological patterns. Although factors driving variation in these elements are well established, expanding stoichiometric principles to explore dynamics of the many other essential elements comprising biological tissues (i.e. the ionome) is needed to determine their metabolic relationships and better understand biological control of elemental flows through ecosystems. In this paper, we report observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
(131 reference statements)
0
17
0
Order By: Relevance
“…Although similar data are becoming available for a few other taxa (e.g. arthropods, Goos et al 2017; fish, Rudman et al 2019; amphibians, Prater et al, 2019), the majority of such work do not characterise ionomic responses to changes in elemental supply. Unlike autotrophs, the responses of metazoan consumer ionomes to changes in inorganic nutrient supply include associated ionomic changes in diet (Jeyasingh & Pulkkinen 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although similar data are becoming available for a few other taxa (e.g. arthropods, Goos et al 2017; fish, Rudman et al 2019; amphibians, Prater et al, 2019), the majority of such work do not characterise ionomic responses to changes in elemental supply. Unlike autotrophs, the responses of metazoan consumer ionomes to changes in inorganic nutrient supply include associated ionomic changes in diet (Jeyasingh & Pulkkinen 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, such changes in one element invariably interacts with other elements in the extracellular or intracellular environment, with important correlated impacts on functional traits of organisms (e.g., Baxter 2015;Jeyasingh et al 2017). Data on such interactions are important to characterize the biogeochemical niches of taxa (Peñuelas et al 2019), and illuminate a wider set of physiological mechanisms that taxa employ to acclimate or adapt to ecosystems with contrasting biogeochemistry (e.g., Goos et al 2017;Prater et al 2019;Rudman et al 2019), including Fe supply. Indeed, Spijkerman et al (2007) found that at high concentrations, Fe binds to the cell membrane of Chlamydomonas and inhibits transport of bulk elements such as P.…”
Section: Introductionmentioning
confidence: 99%
“…A t-test was used to test the effect of iron treatment on the iron content of Daphnia soma and eggs.To explore correlated changes in the ionomes of algae and Daphnia due to iron treatment (and associated shifts in algal and daphniid iron contents), we utilized a nutrient balance approach(Parent et al 2013). As elaborated inPrater et al (2019), this approach enables unbiased estimates of multivariate relationships among elements, which avoid violating common statistical assumptions and can be used to describe and interpret elemental interactions in organismal tissues. Nutrient balances represent orthogonal log contrasts of elements derived from binary partitions of multivariate elemental data projected into Euclidean space.…”
mentioning
confidence: 99%
“…Salamanders represent a large standing stock of nutrients in aquatic systems [108], but the nutrient composition of salamander species may change across ontogenetic stages [109]. Although salamanders usually have a lower capacity of nutrient recycling compared to other aquatic vertebrates such as fish species because excretion rates are higher in fish species [110,111], it is expected that salamanders can be important recyclers of biologically essential nutrients in fishless systems [21,111].…”
Section: Salamanders As Energy Subsides For Higher Trophic Levelsmentioning
confidence: 99%